Public Company Auditing Around the Securities Exchange Act: Historical Lessons for ESG Assurance - Bourveau, Thomas; Breuer, Matthias; Koenraadt, Jeroen K. G.; Stoumbos, Robert (The Accounting Review, 2025)
ABSTRACT We describe the development of public company auditing in the U.S. in the early 20th century to gain perspective on current developments in environmental, social, and governance (ESG) assurance. Using a broad sample of historical annual reports spanning four decades, we document three facts: first, the spread of public company auditing occurred steadily over the span of several decades. Second, audit services were initially heterogeneous but became standardized through the audit profession’s efforts and interactions with private and public actors. Third, the role of regulation in those early developments was seemingly limited to codifying existing practices, as the first federal audit regulation was introduced only late in the development of the profession and did not significantly impact capital markets. Our historical evidence helps us understand how we arrived at today’s widely accepted and highly regulated financial audits. It uncovers parallels to and offers lessons for current developments in ESG assurance. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G18; G34; M42.